Growth, Yield and Nutrient Uptake Capacity of Rice under Different Sulphur Levels - A. K. M. Sajjadul Islam; Md. Shohel Rana; Dr. Md. Mazibur Rahman; Md. Jainul Abedin Mian; Md. Mezanur Rahman; Md. Asif Rahman; Nazmun Naher (Turkish Journal of Agriculture: Food Science and Technology)
Because of using sulphur free fertilizer, rice crop facing tremendous sulphur (S) deficiency throughout the world as well as in Bangladesh. However, farmers of Bangladesh often overlook the importance of sulphur fertilization on rice yield. Therefore, the present study was conducted to investigate the influence of different levels of sulphur on growth, yield attributes and uptake of N, P, K and S by grain and straw of BRRI dhan41 rice variety. The experiment was laid out in randomized complete block design with three replication and eight treatments including control. The result of the study revealed that the highest plant height, panicle length, filled grain was found in T1 (50% RFD of S) treatment, while the utmost number of effective tiller and straw yield was recorded in T5 (150% RFD of S) treatment. Interestingly, maximum grain yield as well as uptake of N, P, K and S by grain and straw was significantly higher in T6 (175% RFD of S) treatment. The highest grain yield of T6 treatment might be due to maximum nutrient use efficiency. However, in all cases control treatment (T0) gave the worst result. The present study clearly indicates that higher rates (175% of the recommended dose) of S along with other fertilizers may be recommended for better growth and yield of BRRI dhan41 in Bangladesh soil.